Putting Parsons's AGIL Theory to Work: Analyzing Local Muslim Change of Economic Power and Financial Inclusion in Purwokerto City, Indonesia - Hastin Tri Utami; Ahmad Dahlan; Akhmad Faozan; Naerul Edwin Kiky Aprianto; Parno; Muhammad Sirajuddin Qahtan Hamdan (Department of Sharia Economics Faculty of Islamic Economics and Business, Universitas Islam Syarifuddin Lumajang, Indonesia, 2026)
This study examines whether urban transformation and increasing economic activity influence the social structure of surrounding communities. The research focuses on the local Muslim community in three major economic centers in Purwokerto City, Banyumas Regency, namely Pasar Wage, Kebon Dalem Market, and the area surrounding the city square (Alun-alun). Purwokerto has experienced rapid economic growth and urban expansion, positioning it as a strategic destination for residents from neighboring regions. This transformation raises important questions regarding its impact on local community dynamics, particularly within Muslim society. Data were collected through observation, documentation, and in-depth interviews with selected informants, and analyzed using Talcott Parsons’ AGIL framework, which includes Adaptation, Goal Attainment, Integration, and Latent Pattern Maintenance. The findings reveal that urban change in Purwokerto encompasses not only economic transformation but also social and political dimensions. The local Muslim community demonstrates a strong capacity for adaptation to economic shifts while actively pursuing economic opportunities. At the same time, social cohesion remains intact through the reinforcement of religious values, social networks, and national identity. These elements function as latent pattern maintenance mechanisms that sustain community stability amid urban change. This study highlights the resilience of local Muslim communities in balancing economic development with the preservation of social and religious values.